Hasil Pengujian Proksimasi Dan Gas Buang Pada Briket Campuran Limbah Serutan Kayu, Sekam Padi Dan Bulu Ayam - Muhamad Rizky Adipratama; Reza Setiawan; Najmudin Fauji (Politeknik Negeri Padang, 2021)
Biomass energy is one that can be used as an alternative energy as a substitute for fossil fuels and can also be useful for reducing environmental pollution due to increasing waste or waste. The manufacture of briquettes from chicken feather waste, wood shavings and rice husk waste aims to help deal with the problem of waste and use it as an alternative fuel. The making of briquettes is carried out by the process of drying the ingredients, charcoal, milling, sieving, kneading, printing, drying, proximate testing and measuring emissions on the briquettes. In this study, the composition of a mixture of chicken feathers (30%, 40%, 50%), wood shavings and rice husk (35%, 30%, 25%) was treated as well as particle sizes of 30 mesh and 60 mesh. The results of this study indicate that the lowest moisture content is in sample B2 of 4.5%. The lowest levels of volatile matters were in sample A1 of 37.4%. The lowest ash content was found in sample B3 at 10.8%. The highest fixed carbon was found in sample A3 at 45.1%. The highest calorific value (Gross Calorific Value) is found in the B3 sample of 5594 Kcal / Kg. And it has the highest CO, CO2, and HC emissions produced from the briquettes, namely 0.24%, 0.8%, 46 ppm. The properties of briquettes that have met SNI standards are moisture content, calorific value (except for sample A1), and the resulting emissions. And those that have not met SNI standards are the levels of volatile matter, ash content and fixed carbon. The resulting briquette can be used because the calorific value obtained is quiet high, which is above the specified standard of ≥ 5000 Kcal/Kg.